Opportunities for Improved HIV Prevention and Treatment through Budget Optimization in Eswatini - Minnery, Mark; Mathabela, Nokwazi; Shubber, Zara; Mabuza, Khanya; Gorgens, Marelize; Cheikh, Nejma; Wilson, David P.; Kelly, Sherrie L. (PLoS, 2020)
Eswatini achieved a 44% decrease in new HIV infections from 2014 to 2019 through substantial scale-up of testing and treatment. However, it still has one of the highest rates of HIV incidence in the world, with 14 infections per 1,000 adults 15–49 years estimated for 2017. The Government of Eswatini has called for an 85% reduction in new infections by 2023 over 2017 levels. To make further progress towards this target and to achieve maximum health gains, this study aims to model optimized investments of available HIV resources.